A new regional balance: Challenges and opportunities for intermediate city regions in Europe - Andreas P. Cornett (European Regional Science Association (ERSA), 2014)
The regional landscape in Europe has changed during the last decades. After a period of conversion, processes of diversion has reentered the scene. In the aftermath of the economic crisis South European countries and regions have suffered due to declining economic activity. The trend toward regional economic convergence has been interrupted, not only in a regional perspective, but also country wise. In particular the latter is a direct impact of the financial crisis and the European debt crisis. A closer look behind the processes of conversion and disparities in the last decades unveils a more complex pattern, also before the current crisis. In most EU countries the trend toward conversion of economic performance between countries disguised an intraregional trend toward polarization, with growing metropolitan regions and shrinking rural areas. Prominent features of this process were outmigration, aging population and a shrinking economic base. Central explanations have to be found in new economic growth theories and structural changes in the international system of production. The purpose of the current paper is to investigate these patterns with special attention on intermediate city regions, usually located in the vicinity of the large urban agglomeration or farer away in the country. The project is both explorative and explanatory, aiming at to detect and define types of ?intermediate city regions' and to identify the drivers of change, based on the above mentioned conceptual anchors. The central research question is to what extent the processes characterizing the urban rural cleavages; also apply to the current situation of intermediate cities. Who are the winners or losers in this polarization process, and what characterize the well performing intermediate city regions? Danish evidence points toward a mixed pattern. Central and economically well-structured city-region can maintain growth; more peripheral located city-regions face problems. In the short and medium term some city regions seems to benefit from restructuring of the public sector in the aftermath of the reform of the regional and municipality organization in Denmark, by attracting workplaces and people form their rural neighborhood. In the longer run the fundamental shift in business and industry away form traditional manufacturing and service toward knowledge intensive service and products may become decisive for the success of these regions.
Keywords: R1; R11; 330; structural change; new economic growth theory; medium-size city regions; processes of conversion and diversion; the new regional (im)-balance